Hormones and human developmental plasticity. (5th April 2020) - Ponzi, Davide; Flinn, Mark V.; Muehlenbein, Michael P.; Nepomnaschy, Pablo A.
Abstract: Natural selection favors the evolution of mechanisms that optimize the allocation of resources and time among competing traits. Hormones mediate developmental plasticity, the changes in the phenotype that occur during ontogeny. Despite their highly conserved functions, the flexibilities of human hormonal systems suggest a strong history of adaptation to variable environments. Physiological research on developmental plasticity has focused on the early programming effects of stress, the hypothalamus-pituitary-adrenal axis (HPAA) and the hypothalamus-pituitary-gonadal axis (HPGA) during critical periods, when the hormones produced have the strongest influence on the developing brain. Often this research emphasizes the maladaptive effects of early stressful experiences. Here we posit that the HPAA and HPAG systems in human developmental plasticity have evolved to be responsive to complex and dynamic problems associated with human sociality. The lengthy period of human offspring dependency, and its associated brain development and risks, is linked to the uniquely human combination of stable breeding bonds, extensive paternal effort in a multi-male group, extended bilateral kin recognition, grandparenting, and controlled exchange of mates among kin groups. We evaluate an evolutionary framework that integrates proximate physiological explanations with ontogeny, phylogeny, adaptive function, and comparative life history data. Highlights: Hormones are important mediators of life-history tradeoffs. Humans have an unusually long period of growth and development, lasting for almost two decades, that has inherent risks. During development, in correlation with several neuroendocrine events, multiple sensitive periods of plasticity have evolved, each uniquely responsive to specific social cues that we suggest were relevant during human evolution. The hypothalamus-pituitary-adrenal axis (HPAA) and the hypothalamus-pituitarygonadal axis (HPGA) are key parts of the neuroendocrine system, both regulating human phenotypic plasticity. Epigenetic mechanisms act as integrators of past and present information relevant to human reproductive strategies through the functions of the HPAA and HPGA.